PENGARUH PROGRAM K3 (KESEHATAN DAN KESELAMATAN KERJA) TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI PT. KERETA API INDONESIA (PERSERO) DAERAH OPERASI 3 CIREBON - Pertiwi, Wike (Fakultas Ekonomi Universitas 17 Agustus 1945 Cirebon, 2019)
Occupational health and safety is one of the important aspects to be considered by human resource management, because remembering human being is an important asset in a company that play a role for progress of company in getting profit. In order to create safe and comfortable conditions and situations in the workplace, every company needs to provide adequate facilities for its workers, in order to protect their physical and mental safety from accidents and illness due to the work they do. So how much attention the company to the safety and health of employees interesting to investigate. Therefore this study aims to analyze the effect of the application of health and safety (K3) programs to increase employees productivity at PT. Kereta Api Indonesia (Persero) area operation 3 Cirebon. This research is a quantitative research with survey method, using questionnaire instrument. Testing the instrument using validity test and reliability test. The sample size of 100 people was obtained from the entire population by using the Slovin formula. Data analysis techniques used by the authors in this study is a simple linear regression analysis with F test and t test, to measure the effect of independent variables on dependent variable that is health and safety program as independent variable (X) and employee work productivity as dependent variable (Y). Based on the calculation of coefficient of determination (KD) is known that the value of R square of 0.10, this means the percentage contribution of variables K3 program (health and safety) to work productivity employees at PT. Kereta Api Indonesia (Persero) Operation Area 3 Cirebon of 10% while the remaining 90% influenced by other variables not examined in this study.